Resting-state blink rate does not increase following very-light-intensity exercise, but individual variation predicts executive function enhancement levels - Ryuta Kuwamizu; Yudai Yamazaki; Naoki Aoike; Dongmin Lee; Hideaki Soya (Journal of Physiological Anthropology)
Abstract Background Acute physical exercise, even at a very-light-intensity, potentiates prefrontal cortex activation and improves executive function. The underlying circuit mechanisms in the brain remain poorly understood, though we speculate a potential involvement of arousal-related neuromodulatory systems. Recently, our rodent study demonstrated that exercise, even at light-intensity, activates the midbrain dopaminergic neurons. Resting-state spontaneous eye blink rate is linked to brain-arousal neural circuits, and potentially to those modulated by dopaminergic system. We hypothesized that neural substrates linked to resting-state eye blink rate contribute to the cognitive impact of acute very-light-intensity exercise. Method We analyzed data from a previous study with a renewed focus on resting-state eye blink rate. Twenty-four healthy young adults completed both 10 min of cycling (very-light-intensity exercise: 30% peak oxygen uptake) and rest conditions. Resting-state eye blink rate and Stroop task performance were measured before and after both exercise and resting control. Results Results showed no significant differences in eye blink rate changes between conditions. However, correlation analyses revealed that exercise-induced changes in resting-state eye blink rate were significantly associated with individual variations in Stroop task performance enhancement. Conclusion Very-light-intensity exercise does not elicit a consistent increase in eye blink rate after exercise. This finding does not support the involvement of a blink increase-linked neural substrate in enhancing executive function through very-light-intensity exercise. However, resting-state eye blink rate that is altered by exercise is predictive of executive function enhancement levels; this may serve as a novel contactless biomarker for predicting exercise benefits for brain health and cognition.